Design and technology in primary school classrooms : developing teachers' perspectives and practices - Tickle, Les (Falmer, 1990)
Design and Technology in Primary School Classrooms presents a comprehensive account of the development and nature of design and technology in the primary classroom from the modest beginnings in the 1980s to detailed implementation within the National Curriculum. It shows how the design/problem solving process and the knowledge, skills and understanding associated with design and technology can be developed by teachers who were previously unfamiliar with such activities. Case studies demonstrate the teaching strategies employed and illustrate in detail how children respond to design and technology in complex ways. The book combines original classroom research data wuth extensive illustrations, resource information and summaries of what design and technology in the National Curriculum involves.